Edukasi Etika Batuk dan Bersin untuk Meningkatkan Perilaku Higienis Anak TK di Ciamis - Firmansyah, Andan; Nurnaziyah, Alimah; Oktavia, Amelia; Rahayu, Budi; Naufal Ramadhan, Daffa; Ahmadi, Mia Laila Salsa; Lisnasari, Novi Mirna (LPPM STIKes Muhammadiyah Ciamis, 2025)
Introduction: Respiratory infections are common among kindergarten children due to close interactions and limited awareness of personal hygiene. Early health education on proper coughing and sneezing etiquette is an important preventive strategy to reduce disease transmission and promote healthy behaviors. Objective: This community service activity aimed to improve the knowledge and skills of kindergarten children at TK Perwanida Ciamis in practicing proper coughing and sneezing etiquette through interactive learning and visual media. Method: The activity was conducted for 45–60 minutes using a participatory approach. Educational materials included illustrated posters, demonstrations, ice-breaking activities, and hands-on practice. Evaluation was conducted through direct observation of children’s ability to correctly perform the techniques. Result: The activity was well received, and most children were able to correctly demonstrate proper coughing and sneezing etiquette after the intervention. Visual media and demonstrations enhanced children’s understanding and engagement. However, continuous reinforcement from teachers and parents is needed to sustain these behaviors. Conclusion: Interactive and visual-based education effectively improved hygiene awareness and practices among kindergarten children. Ongoing support from teachers and parents is essential to maintain these behaviors and prevent respiratory infections.